2008
DOI: 10.1007/s00128-008-9535-1
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Imidacloprid (Premise® 75) in a Tank-Mixed Aqueous Solution When Stored in Shade or Sunlight

Abstract: Polyethylene tanks are commonly used by pest management professionals to mix and apply termiticides. These termiticides are susceptible to rapid photolysis and the ability of application tanks to filter sunlight has been questioned. We investigated the stability of imidacloprid (Premise 75) in aqueous solutions stored in polyethylene tanks under shade or sunlight. Chemical analysis of aqueous solutions sampled at 0, 24, 48, 72, 168 and 336 h revealed that imidacloprid was relatively stable. Our results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Imidacloprid (IMI) is a broad-spectrum neonicotinoid insecticide with excellent systemic and contact activity, low toxicity, and low residue, supporting its widespread application in many agricultural crops . Nevertheless, this pesticide is unstable under UV exposure and will undergo rapid photolysis even when exposed to sunlight, thereby losing its efficacy. , Thus, nanocarrier encapsulation and delivery are of great significance to protect IMI against photolytic decomposition. Among various nanocarriers, thermosensitive and photosensitive release systems are preferred because the release rate and efficacy of IMI is positively correlated with ambient temperature, , which adapts to the increasing tendency of pests under higher temperatures .…”
Section: Introductionmentioning
confidence: 99%
“…Imidacloprid (IMI) is a broad-spectrum neonicotinoid insecticide with excellent systemic and contact activity, low toxicity, and low residue, supporting its widespread application in many agricultural crops . Nevertheless, this pesticide is unstable under UV exposure and will undergo rapid photolysis even when exposed to sunlight, thereby losing its efficacy. , Thus, nanocarrier encapsulation and delivery are of great significance to protect IMI against photolytic decomposition. Among various nanocarriers, thermosensitive and photosensitive release systems are preferred because the release rate and efficacy of IMI is positively correlated with ambient temperature, , which adapts to the increasing tendency of pests under higher temperatures .…”
Section: Introductionmentioning
confidence: 99%
“…The statistical analysis revealed that there was no significant difference between different bottle colors used in this study. A previous study by Spomer et al (2009) also found the concentrations of imidacloprid in a polyethylene tank had no significant difference with that of in a glass jar. Its concentrations remained unchanged although light penetrated the polythene tank and the glass jar in a different manner.…”
Section: Residuals Of Termiticides In Carmentioning
confidence: 71%